Remote Temperature Sensing in Campus: An Internet of Things Environmental Monitoring Application - Mohammad Azam, Siti Fatimah (Universiti Teknologi PETRONAS, 2016)
A remote temperature sensing system is proposed to detect the temperature of certain areas in Universiti Teknologi PETRONAS (UTP) campus. The system incorporates Internet of Things (IoT) concept where the everyday devices are connected to the internet to provide information, and send the feedback based on the information received, thus allowing the devices to communicate with each other. This project is categorized into smart environmental monitoring where the weather, precisely the temperature of the surrounding is measured. The end-users are able to access the real-time information of the measured data through a website. Currently there is no such system available in UTP that monitors the environmental changes. The temperature distribution is not necessarily equal in UTP as it is a vast campus.